Altered Blood Flow Response to Small Muscle Mass Exercise in Cancer Survivors Treated With Adjuvant Therapy - Didier, K. D.; Ederer, A. K.; Reiter, L. K.; Brown, M.; Hardy, R.; Caldwell, J.; Black, C.; Bemben, M. G.; Ade, Carl J. (My University, 2017)
Background-Adjuvant cancer treatments have been shown to decrease cardiac function. In addition to changes in cardiovascular risk, there are several additional functional consequences including decreases in exercise capacity and increased incidence of cancer-related fatigue. However, the effects of adjuvant cancer treatment on peripheral vascular function during exercise in cancer survivors have not been well documented. We investigated the vascular responses to exercise in cancer survivors previously treated with adjuvant cancer therapies. Methods and Results-Peripheral vascular responses were investigated in 11 cancer survivors previously treated with adjuvant cancer therapies (age 58 +/- 6 years, 34 +/- 30 months from diagnosis) and 9 healthy controls group matched for age, sex, and maximal voluntary contraction. A dynamic handgrip exercise test at 20% maximal voluntary contraction was performed with simultaneous measurements of forearm blood flow and mean arterial pressure. Forearm vascular conductance was calculated from forearm blood flow and mean arterial pressure. Left ventricular ejection time index (LVETi) was derived from the arterial pressure wave form. Forearm blood flow was attenuated in cancer therapies compared to control at 20% maximal voluntary contraction (189.8 +/- 53.8 vs 247.9 +/- 80.3 mL.min (1), respectively). Forearm vascular conductance was not different between groups at rest or during exercise. Mean arterial pressure response to exercise was attenuated in cancer therapies compared to controls (107.8 +/- 10.8 vs 119.2 +/- 16.2 mm Hg). LEVTi was lower in cancer therapies compared to controls. Conclusions-These data suggest an attenuated exercise blood flow response in cancer survivors approximate to 34 months following adjuvant cancer therapy that may be attributed to an attenuated increase in mean arterial pressure.
Citation: Didier, K. D., Ederer, A. K., Reiter, L. K., Brown, M., Hardy, R., Caldwell, J., . . . Ade, C. J. (2017). Altered Blood Flow Response to Small Muscle Mass Exercise in Cancer Survivors Treated With Adjuvant Therapy. Journal of the American Heart Association, 6(2), 9. doi:10.1161/jaha.116.004784
Keywords: Arterial Pressure; Blood Flow; Cancer; Exercise; Exercise Physiology; Endothelium-Dependent Vasodilation